Sosialisasi Pembayaran Non Cash pada Masyarakat Penerima Bantuan PKH di Desa Lapeom Kabupaten Timor Tengah Utara - Ernestina Lika; Marlinda Pala Bani; Adi Faisal Aksa; Ismi Andari (Lembaga Pengembangan Kinerja Dosen, 2025)
Modern money offers various conveniences and efficiencies in transactions, which are increasingly popular among the public, especially in this digital era. However, along with its advantages, modern money also poses new challenges such as the potential for misuse of technology, increased risk of hacking, and regulatory issues that have not been fully resolved, so socialization is needed. The purpose of this socialization is to increase the level of financial literacy for the public in using modern money that can be used in everyday life and provide knowledge about how to make non-cash payments using modern money safely.